PENGARUH KEADILAN PAJAK, SISTEM PERPAJAKAN, PEMAHAMAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (TAX EVASION) - Elissa Margaretha; Sri Lestari Hendrayati; Oktobria Y Asi (Universitas Palangka Raya, 2021)
This study aims to analyze the effect of tax justice, taxation systems, tax understanding, and tax sanctions on taxpayers' perceptions of tax evasion ethics on individual taxpayers of West Kotawaringin. The method used in this research is descriptive method and causality verification. This research was conducted by individual taxpayers of Kotawaringin Barat, totaling 100 samples. The statistical test used is the calculation of the Pearson correlation, validity test, reliability test, multiple regression analysis, hypothesis testing and using the SPSS 25.0 for windows application